Phloem-Specific Methionine Recycling Fuels Polyamine Biosynthesis in a Sulfur-Dependent Manner and Promotes Flower and Seed Development . Issue 2 (10th December 2015) - Zierer, Wolfgang; Hajirezaei, Mohammad R.; Eggert, Kai; Sauer, Norbert; von Wirén, Nicolaus; Pommerrenig, Benjamin
Abstract : Phloem-specific methionine recycling is sufficient to overcome sulfur-deficient growth conditions that would otherwise result in polyamine shortage and impair flower and seed development. Abstract: The Yang or Met Cycle is a series of reactions catalyzing the recycling of the sulfur (S) compound 5′-methylthioadenosine (MTA ) to Met. MTA is produced as a by-product in ethylene, nicotianamine, and polyamine biosynthesis. Whether the Met Cycle preferentially fuels one of these pathways in a S-dependent manner remained unclear so far. We analyzed Arabidopsis ( Arabidopsis thaliana ) mutants with defects in the Met Cycle enzymes 5-METHYLTHIORIBOSE-1-PHOSPHATE-ISOMERASE1 (MTI1) and DEHYDRATASE-ENOLASE-PHOSPHATASE-COMPLEX1 (DEP1) under different S conditions and assayed the contribution of the Met Cycle to the regeneration of S for these pathways. Neither mti1 nor dep1 mutants could recycle MTA but showed S-dependent reproductive failure, which was accompanied by reduced levels of the polyamines putrescine, spermidine, and spermine in mutant inflorescences. Complementation experiments with external application of these three polyamines showed that only the triamine spermine could specifically rescue the S-dependent reproductive defects of the mutant plants. Furthermore, expressing gene-reporter fusions in Arabidopsis showed that MTI1 and DEP1 were mainly expressed in the vasculature of all plant parts. Phloem-specific reconstitution of Met Cycle activity in mti1 and dep1 mutant plants was sufficient to rescue their S-dependent mutant phenotypes. We conclude from these analyses that phloem-specific S recycling during periods of S starvation is essential for the biosynthesis of polyamines required for flowering and seed development.